The Right of Privacy and Freedom of the Press: The Concept of Legal Justice in Indonesia - Nasution, Abdul Haris (Faculty of Law, Hasanuddin University, 2019)
This study aims to describe the problems faced by the party who feels aggrieved or impaired by his personal rights due to media coverage. The dilemma arises because based on the legal system of the press, the media are given protection from lawsuits. This is to guarantee the position of freedom of the press in a democratic system. However, the impact that has been caused due to defamation cannot be resolved simply by using the right of reply. This study aims to explore how legal mechanisms provide justice for victims due to media behavior in line with the principle of press freedom in Indonesia. The results show that the Indonesian Press Law does not have a clear system of legal liability. The rule of conduct in the Press Law is absolutely not regulated. Thus, the right of reply that is contained in the media consciousness or